Collaborative Governance Model For Sustainable Village Planning in Kampar District Riau, Indonesia - Aguswan Aguswan; Agus Sukristyanto; Rahmawati Novaria (Jurnal Mamangan, 2024)
Sustainable village planning is a key focus in Indonesia's national development strategy. This concept aims to create a resilient, independent rural community capable of meeting the needs of the current generation without compromising the ability of future generations to meet their own needs. This study aims to present a collaborative governance model for stakeholders in strengthening sustainable village planning discussed in the musrenbang forum, starting at the village, sub-district, district/city level and ending at the provincial level. The formulation of village planning involves various parties (government, private sector, civil society, universities, and mass media) that can provide input, outputs, and benefits for sustainable village development planning . This study uses qualitative research with a descriptive approach. Through collaborative model analysis, stakeholders are encouraged to participate in the decision-making process and its implementation. The collaborative model for village planning can achieve sustainable village development. The key to successful collaboration lies in the commitment of all parties to actively participate and synergize in the village planning process and the determination of village development priorities within the Kampar Regency village development planning forum (Musrenbang).